Strategic objectives and alternatives of industrial and innovative development of Kazakhstan economy at the present stage of social and economic development of the Republic of Kazakhstan (International relations and international law Journal, 2017)
The «green economy» is defined as a successful economy through effective and rational use of natural raw materials funds for the development of the national welfare in accordance with the adoption of international commitments of Kazakhstan and in the interests of future generations. In this article, the author examined the concept of «green economy» as one of the strategic directions of development of Kazakhstan and explored the concept of the transition of Kazakhstan to the «green economy» and the main problems of the global ecosystem. The author analyzed the prerequisites of the strategy of «green economy» in the world, made a list of the main stages of the origin of this concept in the world. Need of creation of «green economy» in Kazakhstan is revealed and proved. In addition, the developed stages of transition of Kazakhstan to «green economy» are produced. Based on the study, the author summarizes basic information on the subject and made conclusions.
Keywords: «green economy»; «green growth»; ecology; contamination; energy; efficiency; sustainable development